2019
DOI: 10.1148/radiol.2019181625
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Short-pulse Ultrasound Delivers Drugs Uniformly across the Murine Blood-Brain Barrier with Negligible Disruption

Abstract: N oninvasively applied pulses of ultrasound and microbubbles can locally deliver molecules to the brain (1,2). Ultrasound has been shown to shrink brain tumors and improve cognitive function in animal models of Alzheimer disease (3-5). However, despite promising results, there remain concerns about potentially harmful effects from permeability changes to the blood-brain barrier (6,7). Focused ultrasound delivers molecules from the bloodstream to the brain by mechanically stimulating the vessels with acoustical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
70
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 28 publications
6
70
1
Order By: Relevance
“…On the contrary, in a recent study, Morse et al have suggested the use of multiple short bursts emitted at high pulse repetition frequency separated by off time in the range of microseconds to improve the safety of drug delivery 39 . The burst defined in this study was composed of 5-cycle short pulses (5 µs) repeated every 800 µs for 10 ms.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, in a recent study, Morse et al have suggested the use of multiple short bursts emitted at high pulse repetition frequency separated by off time in the range of microseconds to improve the safety of drug delivery 39 . The burst defined in this study was composed of 5-cycle short pulses (5 µs) repeated every 800 µs for 10 ms.…”
Section: Discussionmentioning
confidence: 99%
“…microglial activation. 31 To the best of our knowledge, this is the first time that a probe that targets activated microglia has been delivered to the brain in vivo using focused ultrasound.…”
mentioning
confidence: 98%
“…2B), which had been treated using focused ultrasound to deliver the probe, was quantified via the normalised optical density (average fluorescence intensity in the targeted region subtracted by that of the control region). 30,31 In the right hemisphere (Fig. 2C), where no ultrasound treatment had occurred, no fluorescent signal was observed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such pulses have been reported to produce more uniform cavitation activity within the focal area by extending the microbubble lifetime (Pouliopoulos et al 2014), avoiding cluster formation and spreading the microbubble activity in space and time Pouliopoulos 2017). In vivo, rapid short-pulse sequences produce uniform BBB openings that last less than 10 min and do not allow extravasation of inflammation-inducing proteins, such as albumin, into the brain parenchyma (Morse et al 2019). On the other hand, it is more difficult to deliver large therapeutic molecules using short pulses (Choi et al 2011).…”
Section: Discussionmentioning
confidence: 99%